Diseño de estrategias de posicionamiento por categoría de producto en ROMSA importadora para la fidelización de sus clientes - Romero Rovayo, Kerly Xiomara (2025)
The company ROMSA Importadora specializes in the commercialization of sports articles, facing challenges in brand management and positioning strategies. The lack of market recognition has affected its differentiation from competitors, limiting its growth and customer loyalty. For this reason, this research focuses on the design of positioning strategies by product category, aiming to strengthen brand identity and improve consumer perception. Through an analysis of the external and internal environment, the goal is to establish strategies that enhance communication and increase customer loyalty. The results obtained through surveys and interviews highlight the need to implement branding, advertising, and digital strategies. Factors such as visual identity, social media presence, and customer segmentation are key in the positioning process. Thus, the proposal resulting from this research is oriented towards the design of strategies focused on corporate branding, customer experience, and digital marketing. Communication campaigns, social media content, and partnerships with sports influencers are proposed to improve the perception and positioning of ROMSA Importadora in the market.